2016
DOI: 10.1186/s13017-016-0067-4
|View full text |Cite
|
Sign up to set email alerts
|

Damage control operations in non-trauma patients: defining criteria for the staged rapid source control laparotomy in emergency general surgery

Abstract: BackgroundThe staged laparotomy in the operative management of emergency general surgery (EGS) patients is an extension of trauma surgeons operating on this population. Indications for its application, however, are not well defined, and are currently based on the lethal triad used in physiologically-decompensated trauma patients. This study sought to determine the acute indications for the staged, rapid source control laparotomy (RSCL) in EGS patients.MethodsAll EGS patients undergoing emergent staged RSCL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 31 publications
0
59
0
4
Order By: Relevance
“…Presence of severe sepsis/septic shock, acidosis (pH <7.25), hyperlactaemia (≥3 mmol), old age (>70 years old), multiple comorbidities (≥3) have been proposed as criteria for damage-control surgery in non-trauma patients 19. Our patient fulfilled three criteria: severe sepsis, acidosis and hyperlactaemia.…”
Section: Discussionmentioning
confidence: 94%
“…Presence of severe sepsis/septic shock, acidosis (pH <7.25), hyperlactaemia (≥3 mmol), old age (>70 years old), multiple comorbidities (≥3) have been proposed as criteria for damage-control surgery in non-trauma patients 19. Our patient fulfilled three criteria: severe sepsis, acidosis and hyperlactaemia.…”
Section: Discussionmentioning
confidence: 94%
“…For patients suspected of having NOMI on the basis of abdominal physical findings, computed tomography (CT) findings, or laboratory findings, we aggressively performed laparotomy to obtain a definite diagnosis. The primary surgery consisted of resection of the ischemic intestinal tract without anastomosis and open abdominal management to shorten the operation time that allows a systematic search for the progression of intestinal necrosis . We carefully treated and observed the patients for 24–48 h in the intensive care unit so as not to miss the progression of necrosis or ischemia of the intestinal tract.…”
Section: Methodsmentioning
confidence: 99%
“…However, multivariate logistic regression model confirmed that patients with severe sepsis/septic shock causing SIRS, men over the age of 70, lactate ≥ 3, and three or more comorbidities showed survival benefit if managed with rapid source control laparotomy and planned re-exploration (damage control strategy). Interestingly, approximately 50% of patients with severe sepsis/septic shock in the "on-demand" re-laparotomy group, actually required re-exploration [54]. Unfortunately, the most recent study in our investigation involving 164 patients did not specify the type of damage control procedure employed in each case, despite being prospectively done [55].…”
Section: Use Of Damage Control Surgery In the Setting Of Peritonitismentioning
confidence: 94%
“…One of the most recent studies in our review compared two distinct surgical approaches. Damage control encompassing rapid source control laparotomy with planned re-exploration of the open abdomen (n=53 patients) versus single intervention with ondemand re-laparotomy (n=162 patients) [54]. Results showed that, in contrast to the trauma setting, patients who presented with acidosis (pH ≤ 7.25), coagulopathy, and hypothermia had similar mortality rates regardless of the surgical strategy used.…”
Section: Use Of Damage Control Surgery In the Setting Of Peritonitismentioning
confidence: 99%